The Influence of Organic Growing Media Types And Coconut Water on Potato (Solanum tuberosum L.) Shoot Cuttings of Granola Variety - Veri Wilson Toni; Eliyanti Eliyanti; Rainiyati Rainiyati (Jurnal Media Pertanian, 2026)
Potato (Solanum tube~rosum L.) is an important horticultural commodity with incre~asing de~mand; howe~ve~r, national productivity re~mains low. One~ approach to e~nhance~ production is through apical cutting propagation, whose~ succe~ss is strongly influe~nce~d by the~ growing me~dia and growth stimulants. This study aime~d to e~valuate~ the~ e~ffe~cts of diffe~re~nt type~s of organic growing me~dia and coconut wate~r conce~ntrations on the~ growth of Granola potato apical cuttings. The~ e~xpe~rime~nt was conducte~d in the~ Scre~e~n House~ of the~ Potato Se~e~d Ce~nte~r (BBI) in Kayu Aro, e~mploying a two-factorial Comple~te~ly Randomize~d De~sign (CRD). The~ factors te~ste~d we~re~ type~s of growing me~dia (bamboo humus, manure~, and rice~ husk charcoal) and coconut wate~r conce~ntrations (0, 25, 50, 75 mL•L⁻¹). The~ re~sults showe~d that the~ inte~raction be~twe~e~n me~dia type~ and coconut wate~r conce~ntration had no significant e~ffe~ct on most obse~rve~d parame~te~rs, including plant he~ight, numbe~r of le~ave~s, and numbe~r of tube~rs. Howe~ve~r, it significantly affe~cte~d tube~r fre~sh we~ight. The~ apical cuttings use~d we~re~ four-we~e~k-old Granola varie~ty plants de~rive~d from gre~e~nhouse~ cultivation. A mixture~ of bamboo humus, manure~, and rice~ husk charcoal produce~d the~ be~st growth pe~rformance~. A coconut wate~r conce~ntration of 75 mL•L⁻¹ incre~ase~d le~af numbe~r, tube~r count, and tube~r fre~sh we~ight. In conclusion, the~ combination of organic growing me~dia and coconut wate~r can e~nhance~ potato tube~r yie~ld, although its e~ffe~cts vary de~pe~nding on the~ obse~rve~d parame~te~r.